Effect of Buffering Media with Phosphates on Antibiotic Resistance of Lactic Streptococci - Sinha, R. P. (1984)
Buffering complex growth media with inorganic or organic phosphates increased the resistance levels of lactic streptococci to aminoglycoside antibiotics, whereas it increased their sensitivity to erythromycin, penicillin, and tetracycline. The results suggest the need for caution in the selection of media for testing the antibiotic sensitivity of lactic streptococci.